Exiled : From the Killing Fields of Cambodia to California and Back - Cengel, Katya (Book collections on Project MUSE., 2018)
San Tran Croucher's earliest memories are of fleeing ethnic attacks in her Vietnamese village, only to be later tortured in Cambodia by the Khmer Rouge. Katya Cengel met San when San was seventy-five years old and living in California, having miraculously survived the Cambodian genocide with her three daughters, Sithy, Sithea, and Jennifer. But San's family's troubles didn't end after their resettlement in California. As a teenager under the Khmer Rouge, San's daughter Sithy had been the family's savior, the strong one who learned how to steal food to keep them alive. In the United States, Sithy's survival skills were best suited for a life of crime, and she was eventually jailed for drug possession. U.S. immigration law enforces deportation of any immigrant or refugee who is found guilty of certain illegal activities, and San has hired a lawyer to fight Sithy's deportation case. Only time will tell if they are successful. In Exiled Cengel follows the stories of four Cambodian families, including San's, as they confront criminal deportation forty years after their resettlement in the United States. Weaving together these stories into a single narrative, Cengel finds that violence comes in many forms and that trauma is passed down through generations. With no easy answers, Cengel reveals a cycle of violence, followed by safety, and then loss